2013
DOI: 10.1021/nn404920t
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Nanoscale Variations in Photochemical Damage of Polymer/Fullerene Solar Cells with Dissipation Imaging

Abstract: We use frequency-modulated electrostatic force microscopy to track changes in cantilever quality factor (Q) as a function of photochemical damage in a model organic photovoltaic system poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]] (PTB7) and 3'H-cyclopropa[8,25][5,6]fullerene-C71-D5h(6)-3'-butanoic acid, 3'-phenyl-, methyl ester (PC71BM). We correlate local Q factor imaging with macroscopic device performance and show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…Importantly, we also note that the stability of the semiconductor active layer out to nearly 3000 J/cm 2 under illumination in an air environment compares favorably to similar studies of the degradation of all-organic semiconductor active layers, which can show performance degradation at doses of ~400 J/cm 2 . [32][33][34][35][36] These data further show the importance of material engineering of interfacial layers and electrodes to increase efficiencies and stability. 13,37 Figure 2A shows the current density-voltage (J-V) curves of the pre-degraded devices, which were made from films degraded with 0, 1500, 3000, 3400, 3600 and 3800 J/cm 2 photon doses.…”
Section: Resultsmentioning
confidence: 73%
“…Importantly, we also note that the stability of the semiconductor active layer out to nearly 3000 J/cm 2 under illumination in an air environment compares favorably to similar studies of the degradation of all-organic semiconductor active layers, which can show performance degradation at doses of ~400 J/cm 2 . [32][33][34][35][36] These data further show the importance of material engineering of interfacial layers and electrodes to increase efficiencies and stability. 13,37 Figure 2A shows the current density-voltage (J-V) curves of the pre-degraded devices, which were made from films degraded with 0, 1500, 3000, 3400, 3600 and 3800 J/cm 2 photon doses.…”
Section: Resultsmentioning
confidence: 73%
“…They measured changes in cantilever quality factor with frequency-modulated electrostatic force microscopy and discovered that the use of DIO resulted in slower and more uniform device degradation for PTB7:PCBM, consistent with the higher PCE in these devices compared to the device fabricated without DIO. 166 Though the effect of additives on the morphology varies on a case by case basis and careful attention is needed in selecting the additives, a general trend of decreased domain sizes upon use of a solvent additive is observed. However, some polymer systems naturally aggregate into properly sized domains and thus perform better without the use of solvent additives.…”
Section: Solvent Additivesmentioning
confidence: 99%
“…30 These experiments were motivated by our previously reported scanning probe microscopy study of light-and time-dependent conductivity in a thin film of CsPbBr 3 . 35 We used sample-induced dissipation [36][37][38][39][40][41][42][43][44][45][46][47][48][49] and broadband local dielectric spectroscopy (BLDS) 50 to demonstrate for CsPbBr 3 that conductivity shows a slow activated recovery when the light was switched off, with an activation energy and time-scale consistent with ion motion. We concluded that the sample conductivity dynamics were controlled by the coupled motion of slow and fast charges.…”
Section: Introductionmentioning
confidence: 99%